Developing a scale to assess health regulatory focus. (December 2017) - Ferrer, Rebecca A.; Lipkus, Isaac M.; Cerully, Jennifer L.; McBride, Colleen M.; Shepperd, James A.; Klein, William M.P.
Abstract: Rationale: Regulatory focus (i.e., focus on motivation to achieve gains or avoid losses and non-gains) is used to tailor health behavior change interventions, improving efficacy, but is currently assessed by scales that are not health-specific and may capture a version of the construct that is not ideally matched to the rationale for tailoring. Objective: We developed and validated a Health Regulatory Focus Scale (HRFS), which assesses tendencies to avoid negative health consequences (prevention focus) or achieve positive health outcomes (promotion focus). Methods: Across four studies (and a scale development study in supplementary online materials), we established convergent, discriminant, and predictive validity for the HRFS. In studies examining predictive validity, main outcome measures were health behavior intentions, including intentions to reduce alcohol use, quit smoking, eat a healthy diet, exercise, be screened for cancer, and engage in general cancer preventive behaviors. Results: The promotion and prevention sub-scales performed well in confirmatory factor analyses. Single-factor models had significantly poorer fit than models delineating promotion and prevention. The sub-scales were differentially (and only modestly) correlated with related constructs (anxiety, optimism, information avoidance, ambiguity/fatalism). Higher HRFS-Promotion focus generally corresponded with greater health behavior intentions. Conversely, higher HRFS-Prevention focus corresponded with lower health behavior intentions. Associations were largely maintained even when controlling for established regulatory focus measures, supporting the assertion that the HRFS would predict unique variance in health behavior intentions. Conclusion: The HRFS has the potential to improve the precision with which framed health messages change behavior, as it may assess a version of regulatory focus that is more ideally matched to rationale for tailoring interventions. Highlights: Regulatory focus refers to the motivation to achieve gains or avoid losses. Health behavior interventions are tailored to regulatory focus using a general scale. We developed and validated a Health-specific Regulatory Focus Scale (HRFS). We established convergent, discriminant, and (statistical) predictive validity. The HRFS may improve the precision with which health interventions can be tailored.